AN ISLAMIC PERSPECTIVE ON THE FILM “ASSALAMU’ALAIKUM BEIJING ”: A STUDY IN ENGLISH LITERATURE - Hidayat, Tawvicky; Mujibno, Mujibno; Anam, Saiful (Universitas Al-Amien Prenduan, 2025)
This study aims to explore the film